National Categories and Contemporary Historiography - Řezník, Miloš (Dějiny – teorie – kritika, 2024)
This article is concerned with the social and cultural conditions underlying the continuing important role of concepts of national history. This continuing viability means that concepts that are ever more strikingly emerging as an alternative to national histories are actually failing to challenge them and often in fact derive from nationalist categories (regional history as the history of regions within nations and so on). The basic circumstances underlying the demand for national histories continue to be considered problematised, but the importance of national identities for European societies remains one of the decisive factors here. In regard to national histories, therefore, the situation offers historiography an extensive but at the same time very problematic opportunity for the legitimisation of the discipline. The article is focused on European trends specifically since the end of the 1980s with particular attention to Czech historiography. In this context, it then touches on several important discussions and disputes in Czech historiography over the last 15 years.